Preparation of Aluminium dodecaboride (AlB12) powder by Self-propagating High-temperature Synthesis (SHS) - Chao Wang; Xiaoming Cao; Mengge Dong; Lu Zhang; Jianxing Liu; Xiaozhou Cao; Xiangxin Xue (Open Journal of Chemistry - Peertechz Publications, 2021)
Self-propagating High-temperature Synthesis (SHS) process is used to prepare Aluminium dodecaboride (AlB12). The phase analysis results of preparing AlB12 with Al and B2O3 as raw materials show that under air and argon conditions, the self-propagating and acid-washed self-propagating powders all have α-Al2O3 impurities when Mg, Al and B2O3 are used as raw materials. The phase analysis results of the preparation of AlB12 show that under argon conditions, the self-propagating and acid-washed, self-propagating powder has un-removable MgAl2O4 impurities, and the root cause of the low purity of AlB12 prepared by the self-propagating method is the presence of un-removable impurities.